Sikap Siswa Atas Kinerja Guru dalam Pembelajaran dan Motivasi Belajar terhadap Prestasi Belajar Ilmu Pengetahuan Sosial - Nurdin Nurdin; Ajeng Tina Mulyana; Heri Purwosusanto; Tjipto Djurhatono; Irwan Siagian (Asosiasi Dosen Muda Indonesia, 2025)
This study examines the influence of students’ attitudes toward teachers’ performance and learning motivation on learning achievement in social studies among high school students. A quantitative survey approach was employed to explore how internal and external motivational factors, together with perceptions of teacher competence, contribute to academic success. Data were collected through structured questionnaires using a Likert scale and analyzed with multiple linear regression. The findings indicate that both students’ attitudes toward teachers’ performance and their learning motivation positively and significantly affect learning achievement. These results emphasize the crucial role of teachers in creating engaging learning experiences and highlight motivation as a driving force that enhances students’ performance. The study provides insights for educators and policymakers to develop strategies that foster a supportive learning environment and improve students’ academic outcomes.